Shortchanging complexity: Discourse, distortions, and diversity policy in the age of neoliberalism - Arce-Trigatti, Andrea; Anderson, Ashlee (Education Policy Analysis Archives, 2019)
With this paper we explore the practical materialization of select diversity policies in the United States via an analysis of their implementation at different institutional levels. Specifically, using a cultural studies framework that is guided by Stuart Hall’s (1993) concept of distortions, we investigate how discursive conceptualizations of diversity have been translated into educational policy at the federal and state levels. We contend that the complexity of diversity is often inconsistent with existing neoliberal reform trends that embrace standardization and accountability, making meaningful practical applications exponentially more challenging (Manna, 2011; Wong, 2008). Finally, we look to how these analyses might inform future iterations of diversity policy in a time where rapid changes in education policy and characteristically partisan political agendas have become the norm.